The Impact of Marital Discord on the Relationship between Spouses (The International Journal for Scientific Research, 2026)
This study aimed to identify the impact of marital distress on the relationship between spouses. The study adopted the descriptive survey approach and was conducted on a random sample of 104 male and female participants from the cities of Al-Ahsa, Al Khobar, and Dammam in the Kingdom of Saudi Arabia. A questionnaire was used as the data collection instrument after its validity and reliability had been verified. The results showed that the mean score for the dimension of the early signs of marital distress was 2.03 with a standard deviation of 0.85, indicating a moderate to high level of agreement among the participants regarding the association between the early signs of marital distress and the decline in family adjustment, psychological well-being, and harmony between spouses. The mean score for the dimension of identifying patterns of marital distress was 1.55 with a standard deviation of 0.40, indicating that the patterns of marital distress among the participants tended to range from low to moderate. The mean score for the dimension of the effects of marital distress was 1.37 with a standard deviation of 0.72, indicating that the effects of marital distress on husbands and wives in the study sample were relatively low. In addition, the mean score for the dimension of the best methods for preventing marital distress was 2.10 with a standard deviation of 0.71, reflecting the participants' agreement on the importance of the proposed preventive methods in reducing marital distress. The findings also revealed a statistically significant negative correlation between marital distress and the quality of the relationship between spouses, with a Pearson correlation coefficient of 0.41, indicating that as the level of marital distress increases, the quality of the marital relationship decreases. The study recommends paying greater attention to the early detection of indicators of marital distress, addressing it during its early stages, assessing its causes and consequences, and benefiting from evidence-based counseling programs and specialized centers to promote the quality of marital life.
Keywords: Marital Distress; Relationship between Spouses; Impact of Marital Distress; Prevention of Marital Distress; Patterns of Marital Distress